2014
DOI: 10.4162/nrp.2014.8.2.151
|View full text |Cite
|
Sign up to set email alerts
|

In vitrobiological evaluation of 100 selected methanol extracts from the traditional medicinal plants of Asia

Abstract: BACKGROUND/OBJECTIVESIn Asia, various medicinal plants have been used as the primary sources in the health care regimen for thousands of years. In recent decades, various studies have investigated the biological activity and potential medicinal value of the medicinal plants. In this study, 100 methanol extracts from 98 plant species were evaluated for their biological activities.MATERIALS/METHODSThe research properties, including 1,1-diphenyl-2-pic-rylhydrazyl (DPPH) radical scavenging activity, α-glucosidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Medicinal plants contain powerful comfpounds in any of the parts, including the bark, stem, resin, leaf, root, flower, fruit, and seed. Such healing properties of plants cure various health problems [28]. Euphorbia teheranica Boiss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicinal plants contain powerful comfpounds in any of the parts, including the bark, stem, resin, leaf, root, flower, fruit, and seed. Such healing properties of plants cure various health problems [28]. Euphorbia teheranica Boiss.…”
Section: Discussionmentioning
confidence: 99%
“…IC 50 , according to the MTT assay was 850 µg/mL for 24 hours, and 855 µg/mL for 48 hours after treatment. Li et al, reported that whole plant of E. hirta L. showed significant anticancer activity on HT-29 cellline for 24 hours [28]. Also, Patil and Magdum [30], and Sidambaram et al, [31] showed that E. hirta L. had anti-cancer activity on EL-4 mouse lymphoma cell-line and Hep-2 human larynx epithelioma cellline, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…5,38 Previous reports demonstrated the anti-inflammatory effects of the MeOH extracts of G. glabra. 39 To evaluate the anti-inflammatory activities of the 58 compounds, inhibition of LPS-induced NO production in the RAW 264.7 macrophage cell line was assessed. Compounds 4,7,8,15,22,23,26, and 50 at 10 μM inhibited NO secretion by >30% (Table 3).…”
Section: Journal Of Natural Productsmentioning
confidence: 99%
“…Our previous report (26) has demonstrated considerable anti-inflammatory effect of methanolic extracts from different medicinal plants on LPS-stimulated RAW 264.7 macrophages. In particular, the extract from Glycyrrhiza glabra L. root (EGGR), significantly inhibited nitric oxide production.…”
mentioning
confidence: 94%